Indoor air quality and sick building syndrome among staffs in Universiti Sains Malaysia Health Campus, Kubang kerian, Kelantan - Jun, Kok Ern (Universiti Sains Malaysia, 2016)
A comparative cross sectional study was conducted to determine the association between Indoor Air Quality (IAQ) and Sick Building Syndrome (SBS) in USM Health Campus. A total ninety office workers were selected where 45 workers were from Registration Management Complex Building (New building). A set of questionnaire adopted from Industry Code of Practice (1COP) 2010 was used to assess the prevalence of SBS. Meanwhile, IAQ parameters were monitored by using the Handheld 3016 IAQ Particle Counter and Multi Function Ventilation Meter. All IAQ parameters were below the limit standard set by DOSH and USEPA except air velocity in old building which is lower than the acceptable range standard set by DOSH. The level of IAQ parameter for PMio and total particulate matter (TPM) in old building was significantly higher compared to new building (Z= -2.495, p = 0.013) & ( Z = -2.873, p = 0.014). SBS prevalence was 51.1 % for new building while 64.4% for old building, however, the difference was not significant (p 0.05). Besides, there was a significant different of drowsiness among respondents between old and new building As a conclusion, the level of all IAQ for both buildings in USM Health Campus was below the limit standard except air velocity in old building which lower than the acceptable range standard set by DOSH while the prevalence of SBS among staffs was found to be high in both building. Therefore, regular maintenance of ventilation and control measures to ensure a good IAQ should be maintained. Further study is recommended to determine risk factors to prevent high prevalence of SBS.